If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + -4 = 6f + -12 Reorder the terms: -4 + 3f = 6f + -12 Reorder the terms: -4 + 3f = -12 + 6f Solving -4 + 3f = -12 + 6f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-6f' to each side of the equation. -4 + 3f + -6f = -12 + 6f + -6f Combine like terms: 3f + -6f = -3f -4 + -3f = -12 + 6f + -6f Combine like terms: 6f + -6f = 0 -4 + -3f = -12 + 0 -4 + -3f = -12 Add '4' to each side of the equation. -4 + 4 + -3f = -12 + 4 Combine like terms: -4 + 4 = 0 0 + -3f = -12 + 4 -3f = -12 + 4 Combine like terms: -12 + 4 = -8 -3f = -8 Divide each side by '-3'. f = 2.666666667 Simplifying f = 2.666666667
| 9n+5-4n=10 | | 22+6r=4r | | 6=-x+42-2 | | 50=0.10*x | | 5+-20= | | 9x-22+5x-7=180 | | 16x=21x+17+4x^2 | | 9x-22=5x-7 | | (8x+8)+2x=180 | | 42-g=25 | | 1.5x+5y=917 | | -25a-4=3a+2 | | 5/3x=300 | | 6a=1350/a | | 300+50x=900 | | 46+-1=10x+5 | | 3x+26+(-3x)= | | 4-3r+5=45 | | 3w-12=39 | | 56=1+24 | | 9z+9=5 | | 6x=1350/x | | 4(x-1)+60=-40 | | 8+5x=98 | | 270=b+120 | | x-1=4x+1 | | 4(w+7)=-7(2w-2)+8w | | -8-3(p-4)=2p | | 2b+5=49 | | 3(x-4)-6=2(x-8)+6 | | -x-4=-x-4 | | 4w+28=-14w-14+8w |